2016
DOI: 10.1371/journal.pone.0148439
|View full text |Cite
|
Sign up to set email alerts
|

OGR1/GPR68 Modulates the Severity of Experimental Autoimmune Encephalomyelitis and Regulates Nitric Oxide Production by Macrophages

Abstract: Ovarian cancer G protein-coupled receptor 1 (OGR1) is a proton-sensing molecule that can detect decreases in extracellular pH that occur during inflammation. Although OGR1 has been shown to have pro-inflammatory functions in various diseases, its role in autoimmunity has not been examined. We therefore sought to determine whether OGR1 has a role in the development of T cell autoimmunity by contrasting the development of experimental autoimmune encephalomyelitis between wild type and OGR1-knockout mice. OGR1-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Examples of a direct involvement either in autoimmunity, or MS susceptibility and pathogenesis, include GFI1 20 , 21 , ZMIZ1 2 , 22 and NFE2L2 23 . Moreover, CNTNAP2 24 and DDR1 25 are involved in demyelination/remyelination processes and could be indirectly linked to MS, while AHRR 26 , ITGB7 27 , PPIF 28 and GPR68 29 have been studied in the context of EAE. Ultimately, 12 out of the 58 reported DMPs lie within an LD block containing at least one SNP considered as an MS risk according to the GWAS catalog.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of a direct involvement either in autoimmunity, or MS susceptibility and pathogenesis, include GFI1 20 , 21 , ZMIZ1 2 , 22 and NFE2L2 23 . Moreover, CNTNAP2 24 and DDR1 25 are involved in demyelination/remyelination processes and could be indirectly linked to MS, while AHRR 26 , ITGB7 27 , PPIF 28 and GPR68 29 have been studied in the context of EAE. Ultimately, 12 out of the 58 reported DMPs lie within an LD block containing at least one SNP considered as an MS risk according to the GWAS catalog.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the expression of Gpr68 in myeloid-derived cells is required for prostate cancer cell-induced immunosuppression (Yan et al, 2014). GPR68 mice also have impaired T cell responses associated with a reduced frequency and number of dendritic cells (DCs), higher production of nitric oxide by macrophages, and defect in DCs migration to draining lymph nodes (Aoki et al, 2013; D’Souza et al, 2016). There’s also evidence suggesting that GPR68 could be involved in recall of fear conditioning in mice (Huang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GPR68 (OGR1) is a proton-sensing receptor that can detect decreases in extracellular pH during inflammation. It is expressed in macrophages (184), dendritic cells (187), T cells (188), and neutrophils (186) and has a pro-inflammatory function in colitis (189), asthma through activation of dendritic cells (187), and in murine experimental autoimmune encephalomyelitis that regulates T cell responses during autoimmunity (190). This receptor has been described to be able to couple Gaq/11 and Gas and trigger increased intracellular calcium and cAMP (Table 1) (191,192).…”
Section: Gaq/ 11 and Gasmentioning
confidence: 99%